Research methodology topics: Cross-sectional studies - Juliana Zangirolami-Raimundo; Jorge de Oliveira Echeimberg; Cláudio Leone (2018)
In health the most frequent researches are done in the form of observational studies. In this type of scientific research the researchers did not interfere with the phenomena under study, only observed in a systematic and standardized manner, collecting and recording information, data or materials that spontaneously occur at a particular time of the health-disease process, or along its natural evolution, and then proceed with its description and/or analysis. In observational studies normally four types of study design are used: case series studies, cross-section studies, case-control studies and cohort studies. Thus, cross-sectional studies are very useful in descriptive studies when used in studies that are proposed to be analytical, the results must be interpreted by researchers with good experience in that specific field of knowledge, using a lot of caution and common sense.